Effect of IDR deletion on stress tolerance, DON production and sexual/asexual development of F. graminearum. - Yakubu Saddeeq Abubakar (5558399) (2025)
(A) The colony growth of F. graminearum mutants lacking different IDR sequences compared to PH-1. The strains were cultured on CM agar plates for 3 days at 28°C. (B) Graphical representation of the growth inhibition rates of the different IDR mutants due to the various stress factors. The mutants displayed varying degree of stress tolerance. The values presented are means ± SD from three independent experiments. Bars marked with black asterisks are significantly more inhibited than PH-1, while those marked with red asterisks are significantly less inhibited than PH-1 (*, p < 0.05). (C) Deletion of IDRs in SH3 domain-containing proteins does not influence DON production in F. graminearum. The values presented are means ± SD from three independent experiments run in duplicate. ns: non-significant. (D) Deletion of IDR1 (but not IDR2) of FgPin3 compromises sexual development in F. graminearum. The strains were cultured on carrot agar (CA) plates and exposed to near-UV light for 14 days at 19°C. Bar = 500 μm. The experiment was conducted in triplicate. (E) Deletion of IDRs in SH3 domain-containing proteins does not influence conidiation in F. graminearum. The values presented represent mean ± SD. Each strain was counted five times. ns: non-significant. (TIF)